Flexural Behavior of Slabs with Different Anchorage Locations of Longitudinal Reinforcing Bars in a Composite Basement Wall Junction - Sanghee Kim; Ju-Hyun Mun; Jong-Kook Hong; Keun-Hyeok Yang; Soo-Min Kim; Jae-Il Sim (Buildings, 2023)
Although the anchorage location of longitudinal reinforcing bars is a significant design element for flexural behavior, the conventional anchorage method of using longitudinal reinforcing bars has limited applications in new types of structures, such as composite structures. Therefore, this study examined the effect of the anchorage location of longitudinal reinforcing bars on the flexural behavior of slabs at the junctions of developed composite basement walls (SCBW) under monotonic loads at the top free end of the slab. The test results showed that the slab with longitudinal reinforcing bars anchored to the cast-in-place pile (CIP) in the composite basement wall exhibited ductile behavior accompanied by the yielding of the longitudinal reinforcing bars, a relatively wide area of vertical cracks propagating along the slab length, and a plastic plateau flow in the load–deflection relationships. In particular, the slab with longitudinal reinforcing bars anchored to the basement wall experienced severe crack concentration localized at the junction of the composite basement walls and concrete spalling in the basement walls, which resulted in no yielding of the longitudinal reinforcing bars and no cracks in the slab. Consequently, in a slab, it is recommended that longitudinal reinforcing bars be anchored into the CIP by penetrating the steel plate.